A Linguistic-Based Integrative Vocabulary Approach to Improving Students’ Maharah Kalam - Egha Rahma Ramadhanti; Wulan Indah Fatimatul Djamilah (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2026)
Arabic language learning in Madrasah Tsanawiyah still faces the problem of students’ low maharah kalam (speaking skill). One of the factors contributing to this condition is students’ limited vocabulary mastery and the lack of optimal integration between vocabulary learning and speaking practice. Vocabulary is often taught separately and focused on memorization, which causes students to experience difficulties in applying vocabulary in oral communication. This study aims to examine the use of integrative vocabulary materials implemented by teachers in improving students’ maharah kalam skills at a Madrasah Tsanawiyah. This research employed a qualitative approach with a descriptive method and was conducted at a state Madrasah Tsanawiyah. Data were collected through classroom observations, interviews with teachers and students, and documentation of learning activities. The findings indicate that the use of integrative vocabulary materials can improve students’ speaking fluency, confidence in using Arabic orally, and accuracy in vocabulary usage during maharah kalam activities. In addition, this strategy encourages students’ activeness and participation throughout the learning process. This study contributes to the development of Arabic language learning based on integrative vocabulary instruction and provides practical implications for teachers in designing more communicative and contextual learning to enhance students’ speaking skills.